정출된 구치와 대합되는 임플란트의 합병증 - 정연욱(Yeon-Wook Jung); 이수연(Su-Yeon Lee); 김희중(Hee-Jung Kim) (Journal of dental rehabilitation and applied science, 2020)
Purpose: This study investigated the complications and patterns of implants that confronted with the extruded natural teeth. Materials and Methods: Among patients who received implant treatment between 2006 and 2018 at Chosun University Dental Hospital, only implants that had a maintenance period of at least 5 years and that both implants and confronting natural teeth could be measured and compared on a radiograph were selected. They were divided into two groups. Group 1, experimental group consisted of Implants confronting the extruded natural posterior teeth (n = 167: maxilla (Group 1max) = 92, mandible (Group 1man) = 75) and Group 2, control group consisted of Implants confronting the normal natural posterior teeth (n = 656: maxilla (Group 2max) = 272, mandible (Group 2man) = 384). Results: The incidence of complications between Group 1 and Group 2 was statistically significant. In particular, there was a statistically significant difference between the frequency of marginal bone loss and the amount of marginal bone loss. Conclusion: The extruded natural tooth may cause more frequent complications including bone resorption in the opposing implant. 목적: 이 연구는 정출된 자연치와 대합되는 임플란트에 발생하는 합병증과 그 양상에 대해 고찰하여 대합치 정출이 임플란트 합병증에 어떠한 영향을 미치는지에 대해 알아보고자 하였다. 연구 재료 및 방법: 조선대학교 치과병원에서 2006년부터 2018년 사이에 임플란트치료를 받은 환자 중에서 유지관리기간이 최소 5년 이상이면서 구치부 임플란트와 대합되는 자연치가 방사선 사진상으로 측정 및 비교 가능한 임플란트만을 선택하였다. 정출된 구치부 자연치와 대합되는 임플란트를 실험군인 Group 1 (n = 167: 상악(Group 1max) = 92, 하악(Group 1man) = 75)과 정출소견이 없는 구치부 자연치와 대합되는 임플란트를 대조군인 Group 2 (n = 656: 상악(Group 1max) = 272, 하악(Group 1man) = 384)로 분류하였다. 두 그룹 사이에 합병증의 발생빈도와 변연골 흡수에 대해 조사하였다. 결과: Group 1과 Group 2 사이에 합병증의 발생빈도는 통계학적으로 유의성이 있었다. 특히, 상악골의 치조골 소실 빈도와 치조골 소실 양이 통계적으로 유의한 차이를 나타내었다. 결론: 정출된 자연치는 대합되는 임플란트에 골흡수를 비롯한 합병증을 더 빈번하게 유발할 수 있다.